2021
DOI: 10.1002/ps.6528
|View full text |Cite
|
Sign up to set email alerts
|

Epicuticular hydrocarbons of the redbanded stink bug Piezodorus guildinii (Heteroptera: Pentatomidae): sexual dimorphism and alterations in insects collected in insecticide‐treated soybean crops

Abstract: BACKGROUND The redbanded stink bug Piezodorus guildinii (Heteroptera: Pentatomidae) is one of the most important species affecting soybean crops in southern South America. Capillary gas chromatography coupled to mass spectrometry was used to characterize the epicuticular hydrocarbon profiles of field‐collected insects, and to identify differences in their composition between fifth‐instar nymphs and adults, males and females, and between bugs collected in insecticide‐treated and insecticide‐free soybean crops. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 52 publications
0
6
0
1
Order By: Relevance
“…Virgin individuals were analysed at different times from emergence (0-12 h, 12-24 h, 24-36 h), while mated individuals had one age (6-18 h) 9-methylnonacosane. It is known to be part of the epicuticular profile of the redbanded stink bug Piezodorus guildinii (Westwood) (Heteroptera: Pentatomidae), an important pest of soybean crops in South America (Sessa et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Virgin individuals were analysed at different times from emergence (0-12 h, 12-24 h, 24-36 h), while mated individuals had one age (6-18 h) 9-methylnonacosane. It is known to be part of the epicuticular profile of the redbanded stink bug Piezodorus guildinii (Westwood) (Heteroptera: Pentatomidae), an important pest of soybean crops in South America (Sessa et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The only methyl branched alkane recorded in our study was 9-methylnonacosane. It is known to be part of the epicuticular profile of the redbanded stink bug Piezodorus guildinii (Westwood) (Heteroptera: Pentatomidae), an important pest of soybean crops in South America (Sessa et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the composition of CHCs in colonies of social hymenopterans may vary specifically due to environmental factors (Dapporto et al, 2004b;Blomquist & Bagnères, 2010b). Among the environmental variables that can influence chemical composition in different populations of a species are the types of food resources available (Liang & Silverman, 2000;Buczkowski et al, 2005), climatic factors (Menzel et al, 2017), the use of pollutants (Müller et al, 2017;Sessa et al, 2021;Hamida et al, 2021;Schuehly et al, 2021) and even the rate of parasitism (Lorenzi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, changes in the cuticular chemical profile caused by these contaminants have been recently reported in some species of insects. (Müller et al, 2017;Sessa et al, 2021;Hamida et al, 2021), including in Apis mellifera (Schuehly et al, 2021) Pesticide contamination can increase the response of detoxification enzymes such as cytochrome P450, which is also involved in CHC synthesis (Nelson, 2018;Yan & Liebig, 2021). Therefore, the detoxification induced in response to pesticides can alter the synthesis of CHC and be another factor that helps to explain the differences found between the environments, however this hypothesis also needs to be properly investigated.…”
Section: Discussionmentioning
confidence: 99%
“…With the aim of analyzing the cuticular hydrocarbons of P. pythagoricus , the whole body of adult female spiders ( n = 3) was washed with redistilled water for 3 min to remove any water‐soluble contaminants. After being anesthetized with cold, each spider was transferred to a glass tube and submerged in 5 ml of redistilled hexane (Carlo Erba Reagents) for 5 min to extract the total cuticular lipids (Sessa et al, 2021). The hexane volume was reduced under a nitrogen stream, and the hydrocarbons were separated from the total lipids by adsorption chromatography on a minicolumn (10 mm × 5 mm internal diameter) of activated Biosil A (Bio‐Rad Laboratories) and eluted with redistilled hexane (4 ml).…”
Section: Methodsmentioning
confidence: 99%